Prevention of Triglyceridemia by (Non-)Anticoagulant Heparin(oids) Does Not Preclude Transplant Vasculopathy and Glomerulosclerosis - Shrestha, Pragyi; Katta, Kirankumar; Talsma, Ditmer; Naggi, Annamaria; Hillebrands, Jan-Luuk; Sluis, Bart van de; van den Born, Jacob (Frontiers in Cell and Developmental Biology, 2022)
Background: In renal transplantation, chronic transplant dysfunction (CTD) is associated with increased PCSK9 and dyslipidemia. PCSK9 is an enzyme that increases plasma cholesterol levels by downregulating LDLR expression. We recently showed increased PCSK9–syndecan-1 interaction in conditions of proteinuria and renal function loss. Treatment with heparin(oids) might be a therapeutic option to improve dyslipidemia and CTD. We investigated the effects of (non-)anticoagulant heparin(oids) on serum lipids, syndecan-1 and PCSK9 levels, and CTD development. Methods: Kidney allotransplantation was performed from female Dark Agouti to male Wistar Furth recipients. Transplanted rats received daily subcutaneous injections of saline, unfractionated heparin, and RO-heparin or NAc-heparin (2 mg heparin(oid)/kg BW) until sacrifice after 9 weeks of treatment. Results: Saline-treated recipients developed hypertension, proteinuria, and loss of creatinine clearance (all p < 0.05 compared to baseline), along with glomerulosclerosis and arterial neo-intima formation. Saline-treated recipients showed significant increase in plasma triglycerides (p < 0.05), borderline increase in non-HDLc/HDLc (p = 0.051), and ∼10-fold increase in serum syndecan-1 (p < 0.05), without significant increase in serum PCSK9 at 8 weeks compared to baseline. Heparin and non-anticoagulant RO-heparin administration in transplanted rats completely prevented an increase in triglycerides compared to saline-treated recipients at 8 weeks (both p < 0.05). Heparin(oids) treatment did not influence serum total cholesterol (TC), plasma syndecan-1 and PCSK9 levels, creatinine clearance, proteinuria, glomerulosclerosis, and arterial neo-intima formation, 8 weeks after transplantation. Combining all groups, increased syndecan-1 shedding was associated with TC (r = 0.5; p = 0.03) and glomerulosclerosis (r = 0.53; p = 0.021), whereas the non-HDLc/HDLc ratio was associated with the neo-intimal score in the transplanted kidneys (r = 0.65; p < 0.001). Conclusion: Prevention of triglyceridemia by (non-)anticoagulant heparin(oids) neither influenced PCSK9/syndecan-1 nor precluded CTD, which however did associate with the shedding of lipoprotein clearance receptor syndecan-1 and the unfavorable cholesterol profile.